Evaluation of mechanical finishing and polishing techniques on the surface roughness of heat-cured acrylic resins (Research, Society and Development, 2025)
This study aimed to evaluate the impact of different mechanical finishing and polishing techniques on the surface roughness of microwave-polymerized thermally activated acrylic resin (TAAC) samples. For this purpose, 50 samples were prepared in TAAC polymerized by microwave energy and distributed into 5 groups according to the finishing and polishing protocol (n = 10): GC (no treatment), G1 (only drills), G2 (drills and lathe), G3 (drills, sandpaper and lathe) and G4 (drills, rubber and lathe). The surface roughness evaluation was performed by the average of five readings on a portable roughness meter with a measurement path configured with an excursion of 0.25 µm and a speed of 0.5 mm/s. The mean surface roughness values ​​for each group were tabulated and statistically analyzed using the nonparametric Mann-Whitney Rank Sum Test (comparison between experimental and control groups) and Kruskal-Wallis (comparison between experimental groups), with a 95% confidence interval. The surface roughness results show that there was a statistically significant difference between the GC and the other experimental groups (P